KEBERHASILAN MELAKUKAN PERUBAHAN MELALUI ADKAR MODEL Studi Kasus Avnet Information Security Company - Elsye Tandelilin (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2013)
There are many forces that are acting as stimulants for change such as socio-cultural, technological, economic and political and the options essentially fall in four categories: structure, physical setting, technology and people. The application of planned changed sometimes create many resistances for many reasons. There are many tactics have been suggested for use by change agents in dealing with resistance to change. One of the best suggestions is ADKAR MODEL (Awareness, Desire, Knowledge, Ability and Reinforcement). The purpose of this article is to illustrate empirically how ADKAR Model is configured to overcome the resistance of change of Avnet’s employees.  Library researchs were carried out with qualitative approach. The current finding indicate that the application of ADKAR Model was  enabled Avnet’s change agent to  identified why the change was not running well and suggestions to handle it and to identify the changing of many levels (individual, group, inter-group and organization.  Another finding was the model can be optimal reached if every step in this model is running well and fully supported by all management teams and also make it successful and permanently embedded into the organizational operations and business model